Initiation of sacubitril/valsartan shortly after hospitalisation for acutely decompensated heart failure in patients with newly diagnosed (de novo) heart failure: a subgroup analysis of the TRANSITION study. (9th December 2019) - Senni, Michele; Wachter, Rolf; Witte, Klaus K.; Straburzynska‐Migaj, Ewa; Belohlavek, Jan; Fonseca, Candida; Mueller, Christian; Lonn, Eva; Chakrabarti, Arhit; Bao, Weibin; Noe, Adele; Schwende, Heike; et al.
Abstract: Aims: Sacubitril/valsartan has shown efficacy and tolerability in patients with heart failure (HF) and reduced ejection fraction (HFrEF) in the ambulatory setting (PARADIGM‐HF), and following stabilisation of acutely decompensated HF (ADHF) (PIONEER‐HF and TRANSITION). However, data are lacking for the initiation of sacubitril/valsartan in newly diagnosed ( de novo ) HFrEF. Here, we assess the tolerability of initiating sacubitril/valsartan following ADHF in TRANSITION subgroups of patients with a de novo vs. prior diagnosis of HFrEF. Methods and results: TRANSITION randomised 1002 patients to pre‐ and post‐discharge initiation of sacubitril/valsartan (analysis set  n  = 991, following exclusions for mis‐randomisation). In this post‐hoc analysis, tolerability to sacubitril/valsartan [proportion of patients achieving target dose (97/103 mg b.i.d.) at 10 weeks post‐randomisation], adverse events (AEs) and serious AEs (SAEs) were compared in de novo ( n  = 286) and prior HFrEF ( n  = 705) subgroups. More de novo than prior HFrEF patients achieved target dose at Week 10 (56% vs. 45%; relative risk ratio 1.30, 95% confidence interval 1.12–1.52, P  < 0.001), and fewer had SAEs and permanent treatment discontinuations. Initiation of sacubitril/valsartan did not prevent the concomitant initiation and up‐titration of guideline‐directed HF therapies. De novo patients showed faster and greater decreases in N‐terminal pro‐B‐type natriuretic peptide and high‐sensitivity troponin‐T, and lower rates of HF and all‐cause rehospitalisation vs. prior HFrEF. Conclusions: After ADHF, first‐line initiation of sacubitril/valsartan in de novo HFrEF, alongside the initiation of other guideline‐directed therapies, is feasible and is associated with a better risk–benefit profile than in patients with prior HFrEF. Early intervention with sacubitril/valsartan may be considered to delay disease progression in patients with de novo HFrEF. Clinical Trial Registration: ClinicalTrials.gov, NCT02661217.